2-D MEMS Scanner for Handheld Multispectral Dual-Axis Confocal Microscopes - Il Woong Jung; Daniel Lopez; Zhen Qiu; Wibool Piyawattanametha (My University, 2018)
We describe a 2-D microelectromechanical systems (MEMS) scanner for a handheld multispectral confocal microscope for early detection and diagnosis of cervical cancer. This paper is an expansion of work originally reported in the Proceedings of IEEE International Conference on Optical MEMS and Nanophotonics 2012. The MEMS scanner and fabrication process has been designed to improve performance for the dual-axis confocal microscopy architecture. Dual-axis confocal microscopy achieves comparable transverse and depth resolution to high numerical aperture (NA) single-axis confocal microscopy but achieves longer working distance by utilizing low-NA optics. The MEMS scanner has an inner gimbal design with torsional flexures separated from the reflectors to reduce light loss and oxide-free outer axis torsional flexures by utilizing poly vias for electrical access to the inner gimbal electrodes. The devices are large-scale batch fabricated using a double layer silicon-on-insulator (SOI) process and predice postreleasing of dies. The scanner has electrostatic optical deflection angles of 2° for the single-sided inner axis at 75 V and ±3° for the outer axis at 120 V. The device has resonance frequencies of ~2.48 kHz and ~348 Hz for the inner and outer axis torsional modes, respectively. Reflectance and fluorescence images with 650 μm × 800 μm field of view are demonstrated at 15 frames/s. The transverse (axial) resolutions are 4.78 μm (6.2 μm), 5.77 μm (6.2 μm), and 7.45 μm (5.6 μm) for wavelengths of 561, 662, and 781 nm, respectively.
Keywords: Image Processing Techniques and Applications